The multidimensionality of the violence concept: elements for the debate - Arlindo da Silva Lourenço; Renata Marcílio Cândido (Universidade Federal de Santa Catarina, 2017)
The treatment multiplicity of current emergent social issues is infinite; diverse possibilities of theoretical analysis are possible for different issues concerning distinct scholars. Regarding these possibilities, this essay aims to discuss the violence concept based on scholars from psychology, psychoanalysis, sociology and also the education area. Furthermore, this work intends to show the violence phenomenon towards its complex and multifaceted perspective, pointing the educational process towards its humanization commitment, as possibility of reason emancipation and overcoming of human actions, known as violent in this world, which is too fragmented already, whose social relationships are too reified.